IMPLEMENTING BILINGUAL STORY-TELLING PICTURE BOOK TO REINFORCE CHARACTER EDUCATION FOR PRE-SCHOOLERS IN ENGLISH EXTRACURRICULAR ACTIVITY - Triastama Wiraatmaja; Agista Nidya Wardani; Kharisma Naidi Warnanda S. (PROJECT (Professional Journal of English Education), 2021)
Reinforcing character education in the early childhood education or preschooler was deemed important nowadays; however, in order to do so it requires creative yet unique method to pique young pupils’ interest. Therefore, this research intends to elaborate the idea of reinforcing character education by implementing Bilingual Story-Telling Picture Book towards the pupils at one of the preschoolers located in Malang, East Java. This Bilingual Story-Telling Picture Book was composed specifically to teach the students about character education by integrating it with one of extracurricular activities in this school, the English language extracurricular activity. Therefore, this Bilingual Story-Telling Picture Book attempted to not only reinforcing the young pupils’ character education in story telling activity, but also improving their literacy and interest towards English language. Thus, the results indicate that the students were keen on learning English on the story-telling activity delivered by the teacher in charge whilst absorbing the value of character education delivered by the book.